Efficacy and safety of adalimumab in paediatric patients with moderate-to-severe ulcerative colitis (ENVISION I): a randomised, controlled, phase 3 study. (August 2021) - Croft, Nicholas M; Faubion, William A; Kugathasan, Subra; Kierkus, Jaroslaw; Ruemmele, Frank M; Shimizu, Toshiaki; Mostafa, Nael M; Venetucci, Mary; Finney-Hayward, Tricia; Sanchez Gonzalez, Yuri; Bereswill, Mareike; Lazar, Andreas; et al.
Summary: Background: Biologic treatment options are limited for children with ulcerative colitis. The aim of this study was to assess the safety and efficacy of adalimumab in children with moderate-to-severe ulcerative colitis. Methods: The double-blind ENVISION I study was done at 24 hospitals in ten countries. Children (4–17 years) with moderate-to-severe ulcerative colitis despite stable doses of concurrent treatment with oral corticosteroids or immunosuppressants were enrolled. Per the original study design, patients were randomly assigned with an Interactive Voice Response System (IVRS) to receive either high-dose induction adalimumab (2·4 mg/kg [maximum 160 mg] at weeks 0 and 1) or standard-dose induction adalimumab (2·4 mg/kg at week 0 and placebo at week 1); both groups received 1·2 mg/kg (maximum 80 mg) at week 2 and 0·6 mg/kg (maximum 40 mg) at weeks 4 and 6. Patients with partial Mayo score (PMS) response at week 8 (defined as a decrease of two or more points and a decrease of ≥30% from baseline in PMS) were randomly assigned (2:2:1)—using IVRS—to receive either high-dose maintenance adalimumab (0·6 mg/kg weekly), standard-dose maintenance adalimumab (0·6 mg/kg every other week), or placebo up to week 52 (random assignment to the placebo group was ceased mid-trial, as was randomisation in the induction phase with all subsequent patients receiving open-label high-dose induction adalimumab). Coprimary endpoints were the proportion of patients with PMS remission at week 8 (intent-to-treat [ITT]-E population, not including those patients who were not randomised in the induction phase) and full Mayo score (FMS) remission at week 52 in week 8 PMS responders (maintenance ITT-E [mITT-E] population), for which the pooled adalimumab group (patients who received high-dose or standard-dose adalimumab) and the individual dose groups were compared against external adult placebo rates. We report results of the final confirmatory analysis. This trial is registered with ClinicalTrials.gov, NCT02065557 . Findings: 93 children were recruited between Oct 13, 2014, and Sept 5, 2018, to the main study (77 [83%] were randomly assigned [double-blind] to receive high-dose or standard-dose induction adalimumab; 16 [17%] received open-label high-dose induction adalimumab after study design change). At week 8, 74 (80%) children who were PMS responders continued to the maintenance period. 62 (84%) patients were randomly assigned to receive high-dose or standard-dose maintenance adalimumab treatment; 12 (16%) patients received placebo. In patients in the ITT-E population who were randomly assigned to receive high-dose induction adalimumab, a significantly higher proportion of patients were in PMS remission at week 8 (28 [60%] of 47) compared with external placebo (19·8%; p=0·0001). 13 (43%) of 30 patients in the standard-dose induction adalimumab group were in PMS remission at week 8 versus an external placebo rate of 19·8%, but this difference was not significant (p=0·38). Similarly, FMS remission at week 52 in children who were week 8 PMS responders was reported in a significantly higher proportion of patients in mITT-E population who received high-dose maintenance adalimumab (14 [45%] of 31 patients) versus external placebo at week 52 (18·4%; p=0·0001). Nine (29%) of 31 patients in the standard-dose maintenance adalimumab group were in FMS remission at week 52 versus an external placebo rate of 18·4%, but this difference was not significant (p=0·38). Remission rates in the pooled adalimumab groups were significantly better compared with external placebo (PMS remission at week 8: 41 [53%] of 77 patients; p<0·0001; FMS remission at week 52: 23 [37%] of 62 patients; p=0·0001). 21 (23%) of 93 patients in the main study had one or more treatment-emergent serious adverse events during any adalimumab exposure. The most common adverse events were headache, anaemia, and ulcerative colitis flare during the induction period and ulcerative colitis flare, headache, and nasopharyngitis during the maintenance period. Interpretation: Clinically meaningful rates of remission and response were reported in children who received adalimumab in this study. No new safety signals were observed, suggesting that adalimumab is an efficacious and safe treatment option for children with moderate-to-severe ulcerative colitis. Funding: AbbVie.